Implementation Of Asean Human Rights Declaration In The Protection Of Women And Children's Rights - Meilyska Purba (Institute of Computer Science (IOCS), 2020)
Various human rights legal instruments, both international, regional and domestic, has become an agreement to be executed by the state to guarantee the protection of freedom-freedom for every individual. In accordance with the contents of the ASEAN Human Rights Declaration on the 4th principle that